2020
DOI: 10.3389/fcimb.2020.589318
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Respiratory Oxidases: A Targetables Vulnerability of Mycobacterial Bioenergetics?

Abstract: Recently, ATP synthase inhibitor Bedaquiline was approved for the treatment of multi-drug resistant tuberculosis emphasizing the importance of oxidative phosphorylation for the survival of mycobacteria. ATP synthesis is primarily dependent on the generation of proton motive force through the electron transport chain in mycobacteria. The mycobacterial electron transport chain utilizes two terminal oxidases for the reduction of oxygen, namely the bc1-aa3 supercomplex and the cytochrome bd oxidase. The bc1-aa3 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 165 publications
(256 reference statements)
1
22
0
Order By: Relevance
“…While our results stand in contrast to the antibiotic resistance phenotype generated by respiratory deficiency in small colony variants described in Staphylococcus aureus and other species 51 , they are consistent with studies in Mycobacterium tuberculosis in which targeting of the electron transport chain is a promising avenue for the development of novel classes of antibiotics 52 , 53 . In recent years two electron transport chain inhibitors—bedaquiline, an ATPase inhibitor, and pretomanid, a nitric oxide donor and respiratory poison—have been approved by the Food and Drug Administration (FDA) for the treatment of multidrug resistant M. tuberculosis 52 , 54 . Additionally, promising results from a phase 2 clinical trial were recently reported for telacebec (Q203), an inhibitor of the terminal cytochrome oxidase supercomplex bc 1 -aa 3 55 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While our results stand in contrast to the antibiotic resistance phenotype generated by respiratory deficiency in small colony variants described in Staphylococcus aureus and other species 51 , they are consistent with studies in Mycobacterium tuberculosis in which targeting of the electron transport chain is a promising avenue for the development of novel classes of antibiotics 52 , 53 . In recent years two electron transport chain inhibitors—bedaquiline, an ATPase inhibitor, and pretomanid, a nitric oxide donor and respiratory poison—have been approved by the Food and Drug Administration (FDA) for the treatment of multidrug resistant M. tuberculosis 52 , 54 . Additionally, promising results from a phase 2 clinical trial were recently reported for telacebec (Q203), an inhibitor of the terminal cytochrome oxidase supercomplex bc 1 -aa 3 55 .…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, promising results from a phase 2 clinical trial were recently reported for telacebec (Q203), an inhibitor of the terminal cytochrome oxidase supercomplex bc 1 -aa 3 55 . In addition to the known clinical utility of these agents, preclinical studies have identified numerous small molecule inhibitors of all electron transport chain components (NADH dehydrogenases, succinate dehydrogenases, quinol oxidases, ATPase), some of which are known to eradicate even highly drug resistant isolates 52 , 53 . Although the potential for disrupting energetics as a therapeutic approach has not been thoroughly evaluated outside mycobacterial species, in combination with our findings these studies raise the possibility of inhibiting cytochrome bd to treat or prevent urinary tract infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aurachins inhibit electron transfer from ubiquinol-8 to heme b 558 by blocking the quinol binding site that is located close to the membrane surface (Fig. 3a, b ) 34 37 . Although aurachin C and D bind with high affinity to bd oxidases, a reliable IC 50 value for bd -II has not yet been determined 38 .…”
Section: Resultsmentioning
confidence: 99%
“…The M. tuberculosis electron transport chain has recently gained interest as a target space for next-generation antibacterials [ 91 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. M. tuberculosis possesses a branched aerobic respiratory chain.…”
Section: Cytochrome Bd As a Prospective Target For...mentioning
confidence: 99%